Comparison of 2D and 3D gamma analyses. Issue 2 (14th January 2014) - Pulliam, Kiley B.; Huang, Jessie Y.; Howell, Rebecca M.; Followill, David; Bosca, Ryan; O'Daniel, Jennifer; Kry, Stephen F.
Abstract : Purpose: : As clinics begin to use 3D metrics for intensity‐modulated radiation therapy (IMRT) quality assurance, it must be noted that these metrics will often produce results different from those produced by their 2D counterparts. 3D and 2D gamma analyses would be expected to produce different values, in part because of the different search space available. In the present investigation, the authors compared the results of 2D and 3D gamma analysis (where both datasets were generated in the same manner) for clinical treatment plans. Methods: : Fifty IMRT plans were selected from the authors' clinical database, and recalculated using Monte Carlo. Treatment planning system‐calculated ("evaluated dose distributions") and Monte Carlo‐recalculated ("reference dose distributions") dose distributions were compared using 2D and 3D gamma analysis. This analysis was performed using a variety of dose‐difference (5%, 3%, 2%, and 1%) and distance‐to‐agreement (5, 3, 2, and 1 mm) acceptance criteria, low‐dose thresholds (5%, 10%, and 15% of the prescription dose), and data grid sizes (1.0, 1.5, and 3.0 mm). Each comparison was evaluated to determine the average 2D and 3D gamma, lower 95th percentile gamma value, and percentage of pixels passing gamma. Results: : The average gamma, lower 95th percentile gamma value, and percentage of passing pixels for each acceptance criterion demonstrated better agreement for 3D than for 2D analysis for every plan comparison. The average difference in the percentage of passing pixels between the 2D and 3D analyses with no low‐dose threshold ranged from 0.9% to 2.1%. Similarly, using a low‐dose threshold resulted in a difference between the mean 2D and 3D results, ranging from 0.8% to 1.5%. The authors observed no appreciable differences in gamma with changes in the data density (constant difference: 0.8% for 2D vs 3D). Conclusions: : The authors found that 3D gamma analysis resulted in up to 2.9% more pixels passing than 2D analysis. It must be noted that clinical 2D versus 3D datasets may have additional differences—for example, if 2D measurements are made with a different dosimeter than 3D measurements. Factors such as inherent dosimeter differences may be an important additional consideration to the extra dimension of available data that was evaluated in this study.